PROCESSING SYSTEM STATE VALUE OF STUDENT PRIMARY SCHOOL 06 NORTH MERUYA THE EVENING USING MICROSOFT VISUAL BASIC 6.0 - Indrati Sidharini; Ristyawati , SKom , MMSI Ristyawati , SKom , MMSI (Jurnal Sistem Informasi, 2006)
such problems in the school environment on processing report value whichcalculations were still done manually, such as a calculator tool to calculate.The role of computerization is very helpful and beneficial for Mr / Mrs teachers toaccelerate the processing of student value.In this study, the authors try to make a computerized system for processing studentreport value by using Microsoft Visual Basic 6.0.